1999
DOI: 10.1246/cl.1999.1067
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dinuclear Manganese(III) Complexes with Tridentate and Bridging Tetradentate Schiff Base Ligands: Preparation, Properties and Catalase-like Function

Abstract: Novel dinuclear manganese(III) complexes, MnIII2(N-PhO-sal)2(X-sal-m-xylylene) (X = H, 3-MeO) have been prepared by the ligand substitution reaction and characterized, where N-PhOH-salH and X-sal-m-xylyleneH2 denote N-2-hydroxyphenylsalicylideneamine and N,N′-di-substituted-salicylidene-m-xylylenediamine, respectively. These complexes have been found to decompose hydrogen peroxide catalytically (H2O2 /Mn < 100), cycling their oxidation levels between Mn2 (III,III) and Mn2 (II,II) with dioxygen evolution. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…It is found that, the electronic spectrum of Co II complex, ½Co 2 ðL 1 ÞðCH 3 OHÞ 2 Á 2CH 3 OH (3), is consistent with the tetrahedral arrangement [32]. Generally, in the Co II tetrahedral complexes, the spectra usually consist of three bands, which are due to 4 (10), showed that the complex has an octahedral structure. The spectra of Co II octahedral complexes, usually consist of three bands.…”
Section: Schiff Base Complexesmentioning
confidence: 92%
See 2 more Smart Citations
“…It is found that, the electronic spectrum of Co II complex, ½Co 2 ðL 1 ÞðCH 3 OHÞ 2 Á 2CH 3 OH (3), is consistent with the tetrahedral arrangement [32]. Generally, in the Co II tetrahedral complexes, the spectra usually consist of three bands, which are due to 4 (10), showed that the complex has an octahedral structure. The spectra of Co II octahedral complexes, usually consist of three bands.…”
Section: Schiff Base Complexesmentioning
confidence: 92%
“…Molar susceptibilities were corrected for diamagnetism of the component atoms by use of Pascal's constants [15]. The calibration used was Hg[Co(SCN) 4 ]. The thermogravimetric (TG) analysis of the solid complexes were performed using TGA-50H thermogravimetric analyzer (Shimadzu) from ambient to 800°C with a 20°C min )1 heating rate using N 2 atmosphere.…”
Section: Physical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schiff base metal complexes exhibit a wide variety of bioactivities, such as anticonvulsant (Sridhar et al, 2002), antifungal (Bharti et al, 2010), anti-HIV (Pandeya et al, 1999), antiviral and antitumor (Zhang et al, 2009), antimicrobial (Gangani and Parsania 2007), anti-allergic (Mandal et al, 2011), antibacterial (Patai, 1970) properties. These compounds are also useful catalysts for the oxygenation of organic compounds (Nishinaga et al, 1983), redox reactions in bio-processes (Lindoy, 1989), aldol reactions (Maruyama et al, 1995), dye degradation (Nakamura et al, 1999), DNA oxidation (Burrows et al, 1996), and also used for targeting of cancer cells in radiopharmaceuticals (Luo et al, 1998). Some studies have shown that the microbicidal and anticancer properties of ligands are enhanced after linking of Schiff base to the metal centre (Holla et al, 2003;Guo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Schiff base compounds and their complexes are widely applied in enantioselective cyclopropanation of styrenes [17], asymmetric addition of cyanide to aldehydes [18], asymmetric aziridination of olefins [19], enantioselective epoxidation [19,20], regio-selective ring opening of epoxides [21] and as a membrane in ion selective electrode [22][23][24][25][26]. The metal complexes of Schiff bases also finds applications in versatile catalytic reactions for organic synthesis [27][28][29][30], degradation of organic substances [31], in radiopharmaceuticals [32], their ability to reversibly bind oxygen [33] and photochromic properties [34]. Schiff base metal complexes have also found greater applications in biological field.…”
mentioning
confidence: 99%